0865 When Nightmares Occur. (12th April 2019) - Youngren, Westley A; Ostrander, Brooke; Hemmer, Eliza; Hamilton, Nancy
Abstract: Introduction: Posttrauma nightmares (PTNs) are nightmares that begin after a trauma and can reoccur as often as five times per week. As of now, research has yet to identify variables that may explain why PTNs occur on the nights they do. Thus, we conducted an exploratory study (Study-E) to identify variables that may influence their occurrence. Results led us to formulate the Nightmare Cognitive Arousal Processing Model (night-CAP), which suggest that cognitive arousal and sleep latency may influence the occurrence of PTNs. To test this model, a pilot study was conducted (Study-P) to see if fear exposure conditions replicated Study-C. Methods: Study-E collected N =146 observations nested within 27 female sexual assault survivors. Methods used to identify predictors of PTN were pre/post sleep surveys administered to each participant for 6 consecutive days/nights. Study-P collected N =20 observations nested within 10 female participants (non-trauma survivors). Participants were run through a haunted house attraction and then completed pre/post sleep surveys for two consecutive nights. In both studies, participants completed baseline measures of psychopathology and trauma history. Results: Study-E used multi-level modeling to discover that pre-sleep cognitive arousal (PCA; z = 2.39, p < .05) and sleep latency (SL; z = 2.58, p < .01) predicted the occurrence of PTNs. For each unit increase in PCA participants were 1.75 times more likely to experience a PTN. For each unit increase in SL participants were 2.09 times more likely to experience a PTN. In regards to Study-P, the power was to small to conduct MLM, but correlation analyses revealed a significant correlation between PCA and nightmare occurrence ( r = .63, p < .05) and a means-difference test demonstrated there were significantly different levels of PCA ( t = 3.22, p < .05) and SL ( t = 4.90, p < .05) on nights where nightmares occurred. Conclusion: Results of both studies support the night-CAP model by providing evidence that PCA and SL play a pivotal role in the manifestation of nightmares. This information is crucial because it may help improve upon current treatments for PTNs. Support (If Any): None.